Low-Dose Oral Cyclophosphamide and Methotrexate Maintenance for Hormone Receptor-Negative Early Breast Cancer: International Breast Cancer Study Group Trial 22-00 - Colleoni, M (2017)
Purpose: To evaluate the benefit of low-dose cyclophosphamide and methotrexate (CM) maintenance, which previously demonstrated antitumor activity and few adverse effects in advanced breast cancer, in early breast cancer. Patients and methods: International Breast Cancer Study Group (IBCSG) Trial 22-00, a randomized phase III clinical trial, enrolled 1,086 women (1,081 intent-to-treat) from November 2000 to December 2012. Women with estrogen receptor- and progesterone receptor-negative (< 10% positive cells by immunohistochemistry) early breast cancer any nodal and human epidermal growth factor receptor 2 status, were randomly assigned anytime between primary surgery and 56 days after the first day of last course of adjuvant chemotherapy to CM maintenance (cyclophosphamide 50 mg/day orally continuously and methotrexate 2.5 mg twice/day orally on days 1 and 2 of every week for 1 year) or to no CM. The primary end point was disease-free survival (DFS), which included invasive recurrences, second (breast and nonbreast) malignancies, and deaths. Results: After a median of 6.9 years of follow-up, DFS was not significantly better for patients assigned to CM maintenance compared with patients assigned to no CM, both overall (hazard ratio [HR], 0.84; 95% CI, 0.66 to 1.06;P = .14) and in triple-negative (TN) disease (n = 814; HR, 0.80; 95% CI, 0.60 to 1.06). Patients with TN, node-positive disease had a nonstatistically significant reduced HR (n = 340; HR, 0.72; 95% CI, 0.49 to 1.05). Seventy-one (13%) of 542 patients assigned to CM maintenance did not start CM. Of 473 patients who received at least one CM maintenance dose (including two patients assigned to no CM), 64 (14%) experienced a grade 3 or 4 treatment-related adverse event; elevated serum transaminases was the most frequently reported (7%), followed by leukopenia (2%). Conclusion: CM maintenance did not produce a significant reduction in DFS events in hormone receptor-negative early breast cancer. The trend toward benefit observed in the TN, node-positive subgroup supports additional exploration of this strategy in the TN, higher-risk population.